Pengaruh Peggunaan Shopee Later Terhadap Perilaku Konsumtif Mahasiswa Fakultas Ekonomi Dan Bisnis Islam UIN Sumatera Utara - Siti Zahra Khostamarul Aspia Lubis; Almi Rahmadani Siregar; Dini Lestari (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
The aims of this study were first to find out the use of Shopee PayLater among students of the Faculty of Islamic Economics and Business at UIN North Sumatra, second to find out the consumptive behavior of students at the Faculty of Islamic Economics and Business at UIN North Sumatra, third to find out the effect of using Shopee PayLater on consumptive behavior of students at the Islamic Economics and Business Faculty of UIN North Sumatra. This research is a quantitative research, namely research explaining the effect of using Shopee PayLater on the consumptive behavior of students of the Islamic Faculty of Economics and Business, UIN North Sumatra. Based on the results of the study, it was concluded that the effect of using Shopee PayLater on student consumptive behavior, the results showed a Significance value (Sig) of 0.062 > 0.05. So it can be concluded that the Ha hypothesis which states the use of ShopeepayLater has a positive effect on the Consumptive Behavior of Islamic Economics Faculty FEBI Students is accepted while Ho is rejected.